2022
DOI: 10.4143/crt.2021.480
|View full text |Cite
|
Sign up to set email alerts
|

Cost Utility Analysis of a Pilot Study for the Korean Lung Cancer Screening Project

Abstract: The aim of this study was to evaluate the cost utility of a pilot study of Korean lung cancer screening project. Materials and MethodsWe constructed a Markov model consisting of 26 states based on the natural history of lung cancer according to the Surveillance, Epidemiology, and End Results summary stage (localized, regional, distant). In the base case, people aged 55-74 years were under consideration for annual screening. Costs and quality-adjusted life years were simulated to calculate the incremental cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…All the cost-effectiveness ratios estimated by studies in Category 3 except Kim et al, are ICERs as they are incremental comparisons between both alternative screening intervals and alternative candidate age ranges. While Kim et al does consider alternative intervals and age ranges, the reported ICERs are actually ACER comparisons to no screening [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the cost-effectiveness ratios estimated by studies in Category 3 except Kim et al, are ICERs as they are incremental comparisons between both alternative screening intervals and alternative candidate age ranges. While Kim et al does consider alternative intervals and age ranges, the reported ICERs are actually ACER comparisons to no screening [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the ten studies that considered multiple screening intervals assessed annual and biennial screening [ 13 , 27 , 29 , 37 , 39 , 53 56 ]. In these cases, biennial screening offers a lower intensity strategy against which to assess the incremental cost effectiveness of annual screening.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations